Preschoolers’ attention to and learning from on-screen characters that vary by effort and efficiency: An eye-tracking study - Choi, Koeun; Schlesinger, Molly A.; Franchak, John M.; Richert, Rebekah A. (Frontiers in Psychology, 2022)
Prior findings are mixed regarding the extent to which children understand others’ effort in early childhood. Especially, little is known about how character effort impacts children’s selective attention and learning. This study examined preschoolers’ visual attention to and learning from two on-screen characters: One character exerting high effort with low efficiency and another character exerting low effort with high efficiency in solving problems successfully. Children between 3.5 and 6.5 years of age (N = 70) watched a video of the two on-screen characters successfully solving problems. Children’s eye movements were recorded during viewing. Each of the two on-screen characters consistently displayed either high effort/low efficiency or low effort/high efficiency to solve four problems (familiarization). For the final problem (testing), the two characters exerted the same level of effort as each other and used unique solutions to solve the problem. Children then solved the final problem themselves using real objects. Children could selectively use either character’s solution demonstrated in the video. Lastly, children explicitly judged how good the characters were at solving problems. Younger children were more likely to use the solution demonstrated by the character with high effort/low efficiency, whereas older children were more likely to use the solution provided by another character with low effort/high efficiency. Younger children allocated more attention to the high effort/low efficiency character than the low effort/high efficiency character, but this pattern was modified by age such that children’s gaze to the low effort/high efficiency character increased with age. Children’s explicit credibility judgments did not differ by character or child age. The findings are discussed with respect to preschoolers’ understanding of effort and implications for children’s learning from screen media.